Project linking and intervention: a response to the inclusion of people with intellectual disabilities (Original) (Revista científica Olimpia, 2019)
The care of people with special educational needs continues to be a priority within government policies and educational programs that are being carried out in Ecuador. Of particular interest are the linking and intervention projects in the Colleges and careers of the country promote the attention to this sector of the population often lacking resources and supports. In correspondence with the above we report progress of the project Linking and intervention carried out by teachers and students of Physical Culture and Basic Education, the Faculty of Humanities and Education at the Technical University of Ambato, whose focus was on mean the benefits of linking and intervention projects to promote a timely response to the inclusion of people with intellectual disabilities to the practice of physical activities- Sports. Based on a quasi-experimental methodology, with the use of theoretical and empirical methods, the research was developed in two parts: The first diagnosis the progress of students with intellectual disabilities who attend the Specialized Educational Unit of Ambato, while in the second part, it has managed to design a Guide of methodological guidelines, to introduce the practice of Physical Activities - Sports based on the playful activity and in gymnastics in the population under study. The results allowed to unveil the importance and relevance of the project to improve the processes of inclusion of people with intellectual disabilities who attend the educational unit of reference.
Keywords: Project; linking; intervention; inclusion; intellectual disability